An environmentally friendly and green method for separation and determination of eight phenolic acids in raw and processed Tussilagofarfara L. by ultra-high performance supercritical fluid chromatography. Issue 15 (2nd October 2019) - Wang, Na; Jia, Yongming; Li, Guangwei; Wang, Jun; Xue, Di; Liu, Xuewei
Abstract: Phenolic acid as an important active ingredient of traditional Chinese medicine, have received extensive attention due to its various biological activities and pharmacological effects. However, the presence of isomers makes the separation of phenolic acids challenging. In the present study an environmentally friendly, sustainable, lower cost, and green that reduce amounts of organic solventsultra-performance convergence chromatography (UPC 2 ) method was developed for separation and quantification eight phenolic acids. Ultra-high performance supercritical fluid chromatography combines the advantages of supercritical fluid chromatography and ultra high performance liquid chromatography technologies with shorter analysis time, higher resolution and better environmental compatibility. The effects of different chromatographic column, co-solvent, column temperature and back pressure were studied. The BEH column was provided the most suitable separation withgradient elution in 20 min using CO2 as the mobile phase and methanol/acetonitrile (70/30, v/v) with 2% TFA as the co-solvent at a flow rate of 0.4 mL/min. A better and more symmetrical peak shape were obtained. Subsequently, the established method was applied to the quantification of phenolic acids in raw and processed Tussilago farfara L. and validated according to FDA guidelines, showed good precision, accuracy, repeatability and linearity in the concentration range. Our findings confirm that the method could be used as an efficient method for exploring phenolic acids of the quality and separation of traditional Chinese medicine. GRAPHICAL ABSTRACT: